The Influence of Precursor to Activator Ratio and Curing Temperature on Geopolymer Paste with One-Part Method - Widayanti, Ari; Ekaputri, Januarti J.; Amini, Iqlima N.; Petrus, Himawan T. B. M.; Putri, Anandita Ade; Soemitro, Ria A. A.; Handayani, Anjas (Salehan Institute of Higher Education, 2025)
Geopolymer is an eco-friendly material that serves as a sustainable alternative to Portland cement in construction. This binder reduces carbon dioxide emissions from cement production. However, its manufacturing process remains complex and requires professional expertise. This study explores an environmentally friendly cement produced through the “One-Part Method” (or the “just add water” method), which simplifies geopolymer application, making it as user-friendly as Portland cement. However, research on the performance of one-part geopolymers with varying activator contents and curing temperatures remains limited. In this study, Class F fly ash was used as a precursor, combined with a dry activator made from geothermal sludge and sodium hydroxide (NaOH). Two compositions were tested with precursor-to-dry activator ratios of 5:1 (OPG-F5F) and 7:1 (OPG-F7F). The compressive strength was significantly influenced by the Si/Al, Na/Si, Na/Al, and water/solid ratios derived from the precursor and activator. Mechanical properties were analyzed at three curing temperatures: ambient, 40°C, and 60°C. Results showed that OPG-F7F achieved the highest strength at 60°C, reaching 76.1 MPa at 28 days. Mineral analysis before and after steam curing revealed no changes in composition, while morphological analysis indicated that higher temperatures produced a denser geopolymer matrix. These findings demonstrate the strong potential of geopolymer cement as a viable Portland cement replacement using the One-Part Method.